Design And Implementation Of Adversarial Neural Network For Voice Data Processing - Tarigan, Heskyel Pranata (Jurnal Komputer Indonesia, 2023)
In today's digital age, voice data processing has become an important area in information and communication technology. Adversarial Neural Networks (GANs) are one of the recent methods that show great potential in improving the quality and efficiency of voice data processing. This article discusses the design and implementation of GANs for speech data processing, focusing on model architecture, optimization techniques, and performance evaluation. The results show that GANs can produce better speech representations and improve processing quality compared to traditional methods. It also explores the challenges faced in the implementation of GANs and provides recommendations for future development.